2018
DOI: 10.4236/health.2018.103022
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Reflective Practice Skills and Volume of Writing in a Reflective Journal

Abstract: Background: According to the diversification of the health needs and the expansion of health disparities, public health nurses need to improve their practical capabilities, starting from basic education in graduate and undergraduate courses. And Reflective Practice with using reflective journal is one way of improving practical capabilities. The purpose of this study was to investigate the relationship between the volume of reflective journal and the quality of progress in the reflective cycle. Methods: The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Although the clinical practice settings described by participants varied, possibly due to the study’s use of Gibbs’s reflective cycle, the study found that reflection was seen as beneficial for participants' feelings, thoughts, and actions [ [18] , [19] , [20] ]. Participants felt it was meant to reflect on events in clinical practice to help them do things the next time they faced a similar situation [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the clinical practice settings described by participants varied, possibly due to the study’s use of Gibbs’s reflective cycle, the study found that reflection was seen as beneficial for participants' feelings, thoughts, and actions [ [18] , [19] , [20] ]. Participants felt it was meant to reflect on events in clinical practice to help them do things the next time they faced a similar situation [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the clinical practice settings described by participants varied, possibly due to the study’s use of Gibbs’s reflective cycle, the study found that reflection was seen as beneficial for participants' feelings, thoughts, and actions [ [18] , [19] , [20] ]. Participants felt it was meant to reflect on events in clinical practice to help them do things the next time they faced a similar situation [ 20 ]. Generally, for MNS, it is not only necessary to master solid clinical expertise but also to learn the ability to communicate and feedback information [ 33 ] so that learn to reduce the impact of adverse events on personal emotions and to think about clinical events more positive and mature way [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To create high-quality expertise in managing in my classes, I found it necessary to follow a developing the required expertise before moving from one step to the next (Tanaka et al, 2018).…”
mentioning
confidence: 99%